Profit Sharing System in Islamic Banking Before, During, and After Covid-19 Pandemic, any Moderation? - Taudlikhul Afkar; Ulfa Puspa Wanti Widodo; Wisudanto; Lina Rifda Naufalin; Ferry Hariawan (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: Explain the consistency of the implications of NPF on Profitability with Profit-sharing System of Islamic Banking through mudharabah financing and musharakah financing before, during, and after the Covid-19 pandemic. Method: Quantitative approach is used in this study with. The number of observations is 14 Islamic banks in Indonesia. This study uses combined financial statement data time series from the Financial Services Authority (OJK) for the 2018-2024 period. The data analysis technique uses Moderating Regression Analysis (MRA) with the JAMOVI tool to further examine the contribution of NPF before, during, and after the covid-19 pandemic through Slope Analysis. Findings: First finding explains that NPF before and after covid-19 pandemic weakened profitability through profit-sharing system with mudharabah financing, while NPF during the covid-19 pandemic did not weaken profitability. Second finding explains that NPF before and during the covid-19 pandemic did not weaken profitability, while NPF after the covid-19 pandemic weakened profitability through profit-sharing system with musharakah financing. Novelty/Value: Originality of this study is the consistency of the implications of NPF moderation on the profitability of Islamic banks in Indonesia through profit-sharing system with different times, namely before, during, and after the Covid-19 pandemic, because there is not yet consistency in the statement of NPF's role in Islamic Banks before.